Physicochemical and Microbiological Profiles of Commercial Cincalok from West Kalimantan - Risa Nofiani; Puji Ardiningsih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Cincalok, a traditional fermented shrimp product, is prepared with mix small and fresh shrimp, salt, and sugar in a certain ratio incubated for 3-7 days. Different recipes of each the commercial cincalok products obtain different of quality and safety level. The aim of this study is to assess the quality and safety of the commercial cincalok products of West Kalimantan based on their physicochemical and microbiological properties. Seven commercial cincalok products collected from the traditional market of West Kalimantan were analyzed physicochemical (moisture content, pH, free amino nitrogen (FAN), titratable acidity, salt content, glucose content, sucrose content, ethanol content) and microbiological (total number of mesophilic aerobic bacteria (TMABs), total halotolerant bacteria (THBs), endospores bacteria, lactic acid bacteria (LABs), fungi, Enterobacteriaceae, Bacillus cereus, Clostridium perfringens, and Staphylococcus aureus)properties. The mean of moisture content, pH, free amino nitrogen (FAN), titratable acidity, salt content, glucose content, sucrose content, ethanol content for 7 samples was 67.59%, 5.16, 0.60 mM/g, 1.75%, 10.56%,1.30%, 0.49% and 0.59%, respectively. The mean of TMABs, THBs, endospores bacteria, LABs, fungi, and Enterobacteriaceae for 7 samples was 1.19-5.18 log CFU/g and 1.76 log CFU/g, respectively, while B. cereus,C. perfringens, and S. aureus were not detected for all of the samples. The results showed high variation of physicochemical and microbiological properties of the products. Some of the products are safe to ate withoutcooked but the other still contain pathogenic bacteria such as some of the enterobacteriaceae strains.